Carbon(IV)oxide Capture and Sequestration in Nigeria: Prospects and Challenges (2006)
The capture and storage of carbon dioxide (CCS) produced during the combustion of fossil fuels now offers one option for attaining large scale reductions in the emissions of greenhouse gases and thus, promote a clean environment. It is now becoming clear that CCS technologies could promote the use or consumption of fossil fuels than otherwise previously thought. This paper presents an overview of the techniques involved in the capture and sequestration of carbondioxide(CO). The opportunities and the challenges of the application of CCS in Nigeria are considered. It is concluded that the development of gas utilization schemes and power plants makes it imperative for Nigeria togive attention to CCS technologies.